The relationship between computer facility and the performance of employee in Scope International (M) Sdn Bhd / Mohd Asyraf Ahmad Bohani - Ahmad Bohani, Mohd Asyraf (Faculty of Business and Management, 2010)
This research is about the relationship of computer facility and the performance employees in SCOPE. The independent variable such as high speed of internet, updated software and equipment and accessories computer, are being identify in order to make a investigated whether or not these independent variable have significantly and influenced the performance of employees. This research was conducted in SCOPE under trade department Bukit Jalil, 100 questionnaires were distributed and 100 questionnaires were returned. To obtain data, researcher were used two methods that are primary and secondary data. Data analyzed using reliability test, pearson correlation analysis, frequency analysis and regression analysis. The result show, two out of three of the element from independent variable which is high speed of internet and equipment and accessories computer have a significant relationship with performance employees. Meanwhile the other one independent variable is not significantly, there is updated software.